2014
DOI: 10.1007/s00256-014-1999-y
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic sacroiliitis: diagnosis, management and clinical outcome

Abstract: Contrast-enhanced MRI is mandatory for a reliable diagnosis. Abscess formation was observed in approximately half of the MRI-diagnosed sacroiliitis cases and required minimally invasive drainage under CT guidance or frequently open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 18 publications
0
26
0
9
Order By: Relevance
“…Upon other diagnoses that are commonly suggested include sciatica, spondylodiscitis, mechanical low back pain, septic arthritis of the hip and sigmoiditis. Similarly, a significant delay in reaching the diagnosis is also reported by Kucera et al where the patient with the longest delay to diagnosis (115 days) experienced the worst clinical outcome requiring sacroiliac arthrodesis owing to joint damage [ 5 ].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Upon other diagnoses that are commonly suggested include sciatica, spondylodiscitis, mechanical low back pain, septic arthritis of the hip and sigmoiditis. Similarly, a significant delay in reaching the diagnosis is also reported by Kucera et al where the patient with the longest delay to diagnosis (115 days) experienced the worst clinical outcome requiring sacroiliac arthrodesis owing to joint damage [ 5 ].…”
Section: Discussionmentioning
confidence: 76%
“…Computed tomography focuses primarily on morphological changes such as erosions, osteosclerosis, and the mass effect of fluid collection within the joint. As all these are features of chronic sacroiliitis, they cannot contribute to the establishment of an early diagnosis [ 5 ]. Wu et al in their series of patients reported that CT has low sensitivity in detecting pyogenic sacroiliitis, where only 40% of adult patients showed positive findings hence suggesting that CT is more suitable for detecting cortical bone destruction especially in elderly patients with inherent osteoporosis that are more prone to develop cortical bone destruction early in the course of pyogenic sacroiliitis [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microbiological diagnosis of pyogenic scaroilitis can be done by culture of blood and joint fluid aspirate. The most common causative organism is S. aureus, however other organisms like E. coli, Pseudomonas, Salmonella, Streptococcus and M. tuberculosis have been also implicated (18). Treatment of PSI remains drainage of abscess by minimally invasive technique along with appropriate antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of PSI remains drainage of abscess by minimally invasive technique along with appropriate antibiotics. The duration of intravenous antibiotic is generally two weeks, followed by oral antibiotics for 4-6 weeks depending on CRP levels, clinical improvement and radiological clearing of lesion (18). The prognosis is favorable if treated appropriately and repeat MRI after successful treatment may show irregular cortical bones with subchondral sclerosis but without any edema.…”
Section: Discussionmentioning
confidence: 99%
“…Abscesses usually require drainage. A more extensive procedure is necessary if an osseous sequestrum is present [3]. A sequestrum represents a focus of necrotic bone secondary to devascularization and resorption of the surrounding bone, as seen in this case (Figs.…”
Section: Discussionmentioning
confidence: 99%